Europe Calling: A New Definition for Internationalization at Home - Beelen, Jos; Jones, Elspeth (International Higher Education, 2015)
The increasing importance of the concept of internationalization at home is not only manifest in the educational policy of the European Commission, in emerging national policies and in institutional policies of European higher education institutions (HEIs), but most of all in educational practice. Since the existing definition of internationalization at home does not offer much support for those who are working on its implementation, the authors have proposed a new definition that hopefully contributes to lifting the ‘conceptual fog’ that surrounds the internationalization of learning and teaching. The new definition may also help to reach a common understanding of the concept when academics, the key actors in the internationalization of teaching and learning, are joined by both educational and internationalization experts. After all, their joint expertise is needed to build the international and intercultural dimensions of programs of study.